PSEUDO-CAML PERFORMANCE OF THE ASEAN-5’S INNOVATIVE BANKING USING THE PARALLELISM OF MARX, SCHUMPETER, AND CHRISTENSEN INNOVATION CONCEPTS - Eric J. Nasution (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2020)
Routine banking transactions have been practically simplified since the advent of financial technology. The application of ChatPay, AliPay, PayPal, ApplePay, etc. demonstrated a massive use of mobile phones on hand. The use of chat bots and AI replacing the function of bank tellers. Given the cybernetic innovation, the author asks the question, “what is really happening in the business world today?” The three gentlemen, Karl Marx, Joseph Schumpeter and Clayton Christensen theorized in 1867, 1942 and 2013, respectively, about wealth annihilation, creative destruction and disruptive innovation. By employing a descriptive method using secondary data from the BIS, AFIN, Asean fintech reports and scientific literature, including that of non-parametric statistics for interpretation, the study sought to answer three main questions; first, the interpretation of their theories; second, the effects of disruptive innovation, and third, the association of pseudo-CAML and the related FPIs. The study recommended that the Asean banking should continue with the sustainable banking innovations that would combat the development of fintech transactions in addition to its active Asean integration framework.